Pemilihan Dan Pemanfaatan Sampah Rumah Tangga Ditinjau Dari Segi Nilai Ekonomis - Lubna Afifah Azra; Vita Aprilina; Yuha Nadhirah Qintharah (UNIB Press, 2022)
Household waste is the remainder of the process of human activities that is not reused and is considered to be of no use. Many people in Dusun Citeureup I manage their waste by burning it in front or behind their house. Burning garbage is not the right thing because the existing waste has not been separated so that it allows air and soil pollution. The method of implementing this program is counseling, training and mentoring with the practice of composting food waste, making Eco Enzyme leftover fruit peels, and making a vertical cultivation system from used bottles. This program is implemented involving housewives as participants.